Gaya Penulisan Naskah Konten Video Hiburan Dalam Meningkatkan Engagement Instagram PT Lopokopi Digital Shankara - Inas, Amirah; Priatna, Wahyu Budi (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2025)
Instagram has become a major platform in digital marketing strategies based on audiovisual content. This study aims to analyze the writing style of entertainment video content scripts used by PT Lopokopi Digital Shankara in increasing engagement on Instagram. The approach used is descriptive qualitative through observation, interviews, and document studies. This study uses Aristotle's Three-Act Structure theory to analyze the alignment of writing style with storytelling patterns. The results of the study show that Lopokopi's entertainment content script writing style consists of elements of a relaxed and humorous tone, slang and non-standard language diction, short sentence structure and storytelling, hyperbole, and is consistent with a narrative format in the form of hooks, storylines, and punchlines, and is supported by visual elements. This strategy is effective in building emotional engagement with the audience, especially young workers Gen Z and millennials, and increasing Lopokopi's Instagram engagement rate.